2018
DOI: 10.2217/fmb-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Antibiofilm Properties of Ocellatin Peptides Against Multidrug-Resistant Pseudomonas Aeruginosa

Abstract: Ocellatin-PT3 may be promising as a template for the development of novel antimicrobial peptides against P. aeruginosa. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
1
43
1
Order By: Relevance
“…In all three cases, the inhibition of the biofilm did not result in the destruction of cells or the slowing down of their growth. This is very important because, usually, biofilms are insensitive to antibiotics and the increase in the effectiveness of antibiotics is explained by the ability to inhibit biofilm formation [67][68][69], which could explain why the synergistic effect in the case of F2 fractions was more pronounced for the strain forming the biofilm (ATCC 35984).…”
Section: Discussionmentioning
confidence: 99%
“…In all three cases, the inhibition of the biofilm did not result in the destruction of cells or the slowing down of their growth. This is very important because, usually, biofilms are insensitive to antibiotics and the increase in the effectiveness of antibiotics is explained by the ability to inhibit biofilm formation [67][68][69], which could explain why the synergistic effect in the case of F2 fractions was more pronounced for the strain forming the biofilm (ATCC 35984).…”
Section: Discussionmentioning
confidence: 99%
“…Bessa et al [ 45 ] reported that ocellatins isolated from L. pustulatus acted preferentially on clinical isolates of multidrug-resistant P. aeruginosa (MICs 16–256 µg/mL) compared with reference strains (MICs > 520 µg/mL). In particular, ocellatin-PT3 displayed an ability to inhibit biofilm formation (concentrations 4–8 times higher than the MIC) and showed synergistic effects with the antibiotics ciprofloxacin and ceftazidime, so the peptide was proposed as a promising lead molecule for the design and development of novel therapeutic agents against drug-resistant P. aeruginosa biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the test compounds to inhibit the biofilm formation by KP010 (a MDR clinical isolate of K. pneumoniae ) was assessed at the respective MIC, 1 / 2 ×MIC and 1 / 4 ×MIC values in tryptic soy broth (TSB) using the crystal violet assay as previously reported [ 36 , 37 ]. Three independent experiments were performed in triplicate for each condition.…”
Section: Methodsmentioning
confidence: 99%